Analysis of Mathematical Problem-Solving Abilities of Elementary School Students in Bengkulu City - Kristiani, Febri; Susanto, Edi (International Journal of Innovation and Education Research, 2025)
Mathematical problem-solving ability is a fundamental competency in mathematics education that must be developed from the primary education level. This study aims to describe the mathematical problem-solving abilities of fifth-grade elementary school students in Bengkulu City. The research instruments included a mathematics problem-solving test based on number material and interview guidelines. The results of the study showed that most students were in the fair (29.4%) and low (26.5%) categories in their problem-solving abilities (14.7) in the very low category, while for the very high category (8.8%) and high category (20.6%). The main difficulties faced by students were in the planning phase of the solution and the final verification of answers. The differences in student performance between schools indicate the influence of pedagogical and environmental factors. Teacher interviews revealed that the dominant teaching approach was conventional, lacking emphasis on reasoning and higher-order thinking skills. The findings recommend implementing problem-based learning strategies and providing professional development for teachers to design instruction that promotes critical and creative thinking skills.